Low-frequency high-concentration salt corrosion concrete accelerated test method

CN122921901APending Publication Date: 2026-10-16CCCC FOURTH HARBOR ENG INST CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610753833.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-28
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0003]然而,现有加速试验技术普遍存在离子种类单一、浓度切换机制缺失及物理-化学-传输多场耦合不足等问题

Benefits of technology

1.精准模拟多离子协同侵蚀环境:通过配制具有固定摩尔比的氯离子、硫酸根与镁离子的复合盐溶液,真实复现了盐渍土中多相盐分的竞争结晶过程,克服了单一盐分试验的局限性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122921901A_ABST
    Figure CN122921901A_ABST
Patent Text Reader

Abstract

The application discloses a kind of low-frequency high-concentration salt erosion concrete accelerated test method, including three stages: first, high-concentration salt solution is applied to the surface of concrete test piece, so that the visible salt crystal is formed in the surface of test piece and near surface pore;Then, the concrete test piece is executed based on chemical erosion agent wet-dry cycle processing, so that calcium hydroxide Ca (OH) 2 in concrete and hydrated calcium silicate C-S-H occur dissolution reaction, and soluble calcium salt is generated;Finally, the concrete test piece is immersed in low-concentration salt solution to simulate the process of salt dynamic migration and diffusion.The application truly reproduces the multiphase salt crystallization competition mechanism in saline soil environment by the synergistic effect of chemical erosion, salt crystallization pressure and physical disturbance, to provide a rapid screening means for concrete material composition design.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of building material durability testing technology, specifically relating to an accelerated test method for low-frequency, high-concentration salt-corrosion concrete. Background Technology

[0002] As infrastructure construction extends into harsh saline environments such as western salt lakes and coastal areas, the long-term durability of concrete structures under high-concentration, multi-ion coexistence conditions faces severe challenges. Traditional accelerated erosion testing methods for concrete mostly focus on steel reinforcement corrosion behavior or the action mechanism of a single salt (such as sodium chloride or sodium sulfate), making it difficult to effectively simulate the complex degradation processes in actual saline soil environments, such as low-frequency wet-dry cycles, multi-ion synergistic migration, and the coupling of salt crystallization pressure and chemical dissolution. Especially in high-concentration salt environments, Cl... - SO4 2- Mg 2+ The coexistence of key ions not only triggers competitive crystallization of multiple salt phases, but also causes continuous damage to the concrete cementitious system through a dissolution-recrystallization cycle, which places higher demands on the authenticity and predictive ability of accelerated testing methods.

[0003] However, existing accelerated testing techniques generally suffer from problems such as limited ion species, lack of concentration switching mechanisms, and insufficient coupling of physical, chemical, and transport fields. For example, while some methods incorporate multi-factor environmental simulation, they do not clearly define the molar ratios of multiple ions in high-concentration salt solutions or their periodic switching strategies, nor do they establish a directional chemical dissolution stage for the CSH and Ca(OH)2 gel phases. Other schemes, while improving erosion efficiency through negative pressure or atomization, only focus on the effect of single sulfate ions, neglecting the role of Cl- ions. - With Mg 2+ The synergistic deterioration effect on the microstructure of concrete is also a concern. Furthermore, existing methods generally lack quantitative control over the fluid shear stress on the specimen surface, failing to accurately reflect the physical disturbances caused by groundwater seepage or tidal erosion on salt crystallization and pore connectivity, leading to significant discrepancies between experimental results and long-term field performance.

[0004] Therefore, there is an urgent need for a low-frequency, high-concentration salt corrosion accelerated test method that can reproduce the entire process of concrete deterioration in saline soil environment with high fidelity. This method can be achieved by constructing a three-stage closed-loop process of multi-ion high-concentration crystallization, NH4Cl directional dissolution dry-wet cycle, and low-concentration salt diffusion, and by combining low-frequency switching and controllable flow rate disturbance, to realize the systematic simulation of the co-evolution mechanism of chemical dissolution, salt crystallization competition and ion migration. Summary of the Invention

[0005] The purpose of this invention is to provide an accelerated testing method for low-frequency, high-concentration salt-corrosion concrete, which can effectively solve the problems mentioned in the background art.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A method for accelerating the testing of low-frequency, high-concentration salt-eroded concrete includes a closed-loop test procedure consisting of the following three stages: Step S1: Apply a high-concentration salt solution to the surface of the concrete specimen to form visible salt crystals on the surface and in the pores near the surface of the specimen; Step S2: After completing step S1, the concrete specimen is subjected to a dry-wet cycle treatment based on a chemical solvent, so that calcium hydroxide Ca(OH)2 in the concrete reacts with calcium silicate hydrate CSH to generate soluble calcium salts. Step S3: Immerse the concrete specimen in a low-concentration salt solution to simulate the dynamic migration and diffusion process of salt. The high-concentration salt solution and the low-concentration salt solution are applied alternately at a set period to form a low-frequency switching; the solution flow rate is adjusted throughout the test to act on the surface of the specimen to simulate the physical disturbance caused by groundwater seepage or tidal erosion; the entire closed-loop test process constitutes an accelerated test system that integrates chemical action, physical damage and ion transport, and is used to guide the design of concrete material composition.

[0007] Furthermore, in step S1, the high-concentration salt solution contains Cl. - SO4 2- Mg 2+ Furthermore, the three components coexist in a fixed molar ratio; in step S2, the chemical solvent is NH4Cl, which provides soluble ions during the wet-dry cycle wetting stage; in step S3, the ionic composition of the low-concentration salt solution is the same as that of the high-concentration salt solution, but the concentration is significantly reduced.

[0008] Furthermore, the alternation between step S1 and step S3 satisfies the low-frequency condition: the switching period T is not less than 7 days, and the switching frequency f is expressed as f = 1 / T, and is not greater than 0.14 times / day; the solution flow rate ranges from 0.5 m / s to 2.0 m / s.

[0009] Further, step S1 specifically includes: applying a salt solution with a total salt concentration of 5 to 10 times that of standard seawater, wherein the standard seawater salt concentration is 35 g / L; the high-concentration salt solution contains Cl... - SO4 2- Mg 2+ The molar ratio is 2:5:2; the duration of step S1 is 7 to 30 days.

[0010] Furthermore, step S2 specifically includes: after step S1, the specimen is placed in a constant temperature and humidity environment for drying for 24 hours, and then immersed in NH4Cl solution for 2 hours to form a dry-wet cycle; this cycle is repeated 5 to 10 times; the molar concentration of the NH4Cl solution is 0.5 mol / L to 2.0 mol / L; the pH value of the NH4Cl solution is maintained at 4.5 ± 0.2.

[0011] Furthermore, step S3 specifically includes: applying a low-concentration salt solution with a total salt concentration of 0.1 times that of standard seawater; wherein the low-concentration salt solution contains Cl... - SO4 2- Mg 2+ The concentrations are 0.1 times the corresponding ion concentrations in the high-concentration salt solution; the duration of step S3 is 7 to 30 days.

[0012] Furthermore, the solution flow rate remains stable when both the high-concentration salt solution and the low-concentration salt solution are applied, and the fluctuation range does not exceed ±0.1 m / s; the solution flow rate is set so that the shear stress on the specimen surface is maintained within the range of 0.8 Pa to 3.2 Pa.

[0013] Furthermore, the concrete specimens were prepared using the actual engineering mix proportions, with a water-cement ratio not exceeding 0.45; after standard curing for 28 days, the specimens were dried in a 60°C oven to constant weight before entering the first stage of testing.

[0014] Furthermore, the experimental method does not collect or analyze parameters related to steel corrosion; all performance evaluations are based on the concrete itself, including: XRD quantitative phase analysis, MIP pore structure test, three-point bending strength, fracture energy, and microcrack connectivity under scanning electron microscopy (SEM).

[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. Accurate simulation of multi-ion synergistic erosion environment: By preparing a composite salt solution with a fixed molar ratio of chloride ions, sulfate ions and magnesium ions, the competitive crystallization process of multiphase salts in saline soil is realistically reproduced, overcoming the limitations of single salt experiments.

[0016] 2. Effective coupling of chemical dissolution and physical damage: The innovative combination of the ammonium chloride chemical dissolution stage with physical scouring under controlled flow rate simultaneously achieves chemical softening and physical erosion of concrete during the acceleration process, simulating the coupled degradation mechanism in the real environment.

[0017] 3. Low-frequency cycling ensures simulation realism: Setting a solution switching cycle of no less than 7 days avoids the non-physical acceleration effect caused by high-frequency cycling, ensuring that salt migration and reaction have a time scale consistent with the actual environment, and significantly improving the accuracy of long-term performance prediction.

[0018] 4. Establish a multi-dimensional evaluation system for concrete: Focusing entirely on the concrete material itself, a multi-scale evaluation method involving phase, pore structure, mechanical properties, and micromorphology is used to systematically reveal its degradation patterns, providing direct experimental basis for the material composition design of concrete under salt crystallization-dissolution conditions. Attached Figure Description

[0019] Other features, objects, and advantages of the present invention will become more apparent from the following detailed description of non-limiting embodiments with reference to the accompanying drawings.

[0020] Figure 1 This is a schematic flowchart of an accelerated testing method for low-frequency, high-concentration salt-corrosion concrete provided in an embodiment of the present invention. Detailed Implementation

[0021] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments.

[0022] Example 1

[0023] like Figure 1 As shown, Embodiment 1 of the present invention discloses an accelerated testing method for low-frequency, high-concentration salt-eroded concrete, comprising the following steps: Step S1: Apply a high-concentration salt solution to the surface of the concrete specimen to form visible salt crystals on the surface and in the pores near the surface of the specimen.

[0024] Specifically, step S1 includes the following refinement operations to achieve accurate simulation of the high-concentration salt corrosion crystallization process: Step S11: Apply a salt solution with a total salt concentration of 5 to 10 times that of standard seawater, wherein the standard seawater salt concentration is 35 g / L; the high-concentration salt solution contains Cl - SO4 2- Mg 2+ The molar ratio is 2:5:2; the duration of step S1 is 7 to 30 days.

[0025] Specifically, the high-concentration salt solution is first prepared. Taking the preparation of a 1L solution with a total salt concentration of 262.5 g / L (i.e., 7.5 times the standard seawater salt concentration) as an example, according to Cl... - SO4 2- Mg 2+ Given a molar ratio of 2:5:2, calculate the required Cl.- SO4 2- Mg 2+ The molar concentration. In this embodiment, SO4²⁻ is set as the target dominant ion, with a concentration of 1.0 mol / L, then the Cl⁻ concentration is 0.4 mol / L, and Mg... 2+ The concentration is 0.4 mol / L. Accordingly, analytical grade sodium chloride (NaCl), analytical grade sodium sulfate (Na2SO4), and analytical grade magnesium chloride hexahydrate (MgCl2·6H2O) are precisely weighed and dissolved together in deionized water, then stirred thoroughly in a 25°C constant temperature water bath until completely clear. The pH of the solution is naturally maintained at 6.8±0.3. It should be noted that the molar ratio design of this invention aims to simulate the increased sulfate ratio due to evaporation enrichment in saline soil environments, rather than directly replicating the composition of seawater. The pretreated concrete specimen is vertically fixed in a corrosion-resistant plexiglass test tank, with the exposed surface of the specimen facing the fluid inlet. A high-precision peristaltic pump system is started to deliver the high-concentration salt solution, kept at a constant temperature of 20±1°C, to the specimen surface at a set stable flow rate. In this invention, the solution application process in step S1 is a dynamic flow mode, rather than static soaking, aiming to simulate the transport effect of groundwater seepage on salts through flowing solution, while avoiding the formation of a concentration boundary layer on the specimen surface due to static placement. The process involves continuous application of the sulfate solution for 7 to 30 days, allowing visible salt crystals to form on the surface and in the pores near the surface of the specimen. This process aims to preferentially penetrate the concrete pores and crystallize out, creating initial damage conditions for subsequent chemical dissolution.

[0026] Step S12: The alternation between step S1 and subsequent step S3 satisfies the low-frequency condition: the switching period T is not less than 7 days, and the switching frequency f is expressed as f = 1 / T, and is not greater than 0.14 times / day; the solution flow rate is in the range of 0.5 m / s to 2.0 m / s.

[0027] Specifically, during the execution period of step S1, the solution flow rate is monitored in real time by an electromagnetic flowmeter, and the peristaltic pump speed is dynamically adjusted by the PLC system to strictly control it within the range of 0.5 m / s to 2.0 m / s, with a fluctuation range not exceeding ±0.1 m / s. The unit of the flow rate v is meters per second (m / s). The flow rate setting not only controls the material transport rate but also forms a low-frequency switching cycle with the subsequent step S3. The duration of step S1 is at least 7 days to ensure sufficient time for stable salt crystal formation, thereby forming a low-frequency alternation with the subsequent low-concentration stage (step S3) with a cycle of not less than 7 days. For example, when step S1 lasts for 10 days and step S3 lasts for 10 days, the switching cycle T is 20 days, and the frequency f = 0.05 times / day, meeting the low-frequency requirement. The beneficial effect is that the low-frequency switching avoids the unsteady pseudo-diffusion caused by frequent concentration changes, making the changes in the humidity field and ion concentration field inside the concrete closer to the slow process under natural conditions.

[0028] Step S13: The solution flow rate remains stable when the high-concentration salt solution and the low-concentration salt solution are applied, and the fluctuation range does not exceed ±0.1m / s; the solution flow rate is set so that the shear stress on the surface of the specimen is maintained within the range of 0.8Pa to 3.2Pa.

[0029] Specifically, the solution flow rate The stability control directly determines the intensity of physical disturbance on the specimen surface, i.e., shear stress. Its unit is Pascal (Pa). The formula for calculating shear stress τ is:

[0030] in, The density of the solution is expressed in kilograms per cubic meter (kg / m³). The coefficient of friction is given for the relatively smooth concrete surface at the beginning of the test. The value is 0.005. According to the above formula, when v = 0.5 m / s, the calculated value is... ≈0.8Pa; when v=2.0m / s, ≈3.2 Pa. Therefore, by controlling the flow velocity between 0.5 m / s and 2.0 m / s, the shear stress on the specimen surface can be controlled. The pressure range is from 0.8 Pa to 3.2 Pa. This physical disturbance effectively simulates the mechanical erosion of the precipitated salt crystal layer by groundwater seepage or tidal erosion, and promotes the migration of the solution into the deeper pores. The beneficial effect is that it introduces a controllable physical damage mechanism, causing salt crystals to accumulate not only on the surface but also within the internal pores, thus more realistically reproducing the spatial distribution characteristics of salt crystallization pressure in the field.

[0031] Step S14: The concrete specimens are prepared using the actual engineering mix proportions, with a water-cement ratio not exceeding 0.45; after standard curing for 28 days, the specimens are dried in a 60°C oven to constant weight before entering the first stage of testing.

[0032] Specifically, the concrete specimens were prepared according to commonly used engineering mix proportions. For example, a typical mix proportion is: 320 kg / m³ cement, 80 kg / m³ fly ash, 60 kg / m³ mineral powder, 780 kg / m³ sand, 1050 kg / m³ crushed stone, 180 kg / m³ water, and 6.0 kg / m³ high-performance water-reducing agent. The calculated water-cement ratio is 180 / (320+80+60)=0.39, which meets the requirement of not exceeding 0.45. The specimen dimensions are 100 mm × 100 mm × 400 mm prisms, without internal reinforcement. After curing under standard conditions (temperature 20±2°C, relative humidity ≥95%) for 28 days, the specimens are transferred to a 60°C forced-air oven to dry to constant weight. The criterion for determining constant weight is: the difference in mass between two consecutive weighings (24 hours apart) does not exceed 0.1% of the initial dry weight of the specimen. The pretreated and dried specimens immediately proceed to step S1 to ensure consistent initial moisture content. Using actual engineering mix proportions and unreinforced specimens allows the evaluation system to focus entirely on the salt corrosion resistance of the concrete material itself, eliminating the interference of steel reinforcement corrosion, resulting in more targeted and universal conclusions.

[0033] By executing steps S11 to S14, step S1 enables the rapid establishment of a salt-rich zone and the induction of crystallization damage within the concrete under the synergistic effect of a high-concentration salt solution and controllable physical shear stress, thus creating conditions for subsequent chemical corrosion. The overall beneficial effect is the efficient activation of multiple degradation mechanisms.

[0034] Step S2: After completing step S1, the concrete specimen is subjected to a wet-dry cycle treatment based on a chemical solvent, so that calcium hydroxide Ca(OH)2 in the concrete reacts with calcium silicate hydrate CSH to form soluble calcium salt.

[0035] Specifically, step S2 includes the following refinement operations to simulate the modification of the microstructure of concrete by chemical erosion: Step S21: After step S1, the specimen is placed in a constant temperature and humidity environment for drying for 24 hours, and then immersed in NH4Cl solution for 2 hours to form a dry-wet cycle; this cycle is repeated 5 to 10 times; the molar concentration of the NH4Cl solution is 0.5 mol / L to 2.0 mol / L; the pH value of the NH4Cl solution is maintained at 4.5±0.2.

[0036] Specifically, immediately after step S1, the specimen is transferred to a constant temperature and humidity curing chamber and dried for 24 hours at a temperature of 20±2°C and a relative humidity of 60±5%. This process promotes the evaporation of moisture from the capillaries inside the specimen, creating a negative pressure gradient. Subsequently, the specimen is completely immersed in a pre-prepared NH4Cl solution for 2 hours. The molar concentration of the NH4Cl solution ranges from 0.5 mol / L to 2.0 mol / L, corresponding to a mass concentration range of 26.75 g / L to 107.0 g / L. The solution is prepared using analytical grade NH4Cl solid and deionized water, and the pH value is precisely adjusted and maintained at 4.5±0.2 using dilute hydrochloric acid or ammonia. This process is monitored by an online pH electrode. Drying and immersion constitute one cycle, which is repeated 5 to 10 times. NH4Cl hydrolyzes under acidic conditions to produce H2O. + It reacts with Ca(OH)2 in concrete: Ca(OH)2 + 2H+ + →Ca 2+ +2H2O; at the same time, NH4+ + Ion exchange with CSH leads to the depolymerization of its structure. This process significantly consumes the alkaline buffering material and cementitious phase of concrete, expands the pore volume, creates more unobstructed channels for subsequent salt migration, and simulates the dissolving effect of acidic substances in the natural environment.

[0037] Step S22: In step S2, the chemical solvent is NH4Cl, which provides soluble ions during the wet-dry cycle wetting stage.

[0038] Specifically, this step further clarifies and emphasizes the type of chemical etchant used in step S21. NH4Cl, as the etchant, simultaneously provides H₂ during the wetting stage. + and NH4 + Two corrosive ions. H + It directly participates in acid-base neutralization reactions, rapidly consuming Ca(OH)2 and NH4. + Through ion exchange, it can more persistently erode CSH gel. The synergistic effect of both achieves efficient and targeted dissolution of the main hydration products of concrete. The beneficial effect is that NH4Cl can achieve significant chemical dissolution within a short wet-dry cycle, effectively accelerating the experimental process. At the same time, its reaction products are mostly soluble salts, avoiding the introduction of difficult-to-identify complex new phases.

[0039] By performing steps S21 and S22, step S2 achieves chemical softening of the concrete matrix and directional modification of its pore structure. The overall beneficial effect is to create a structurally vulnerable period, amplifying the destructive effects of subsequent salt migration and crystallization expansion.

[0040] Step S3: Immerse the concrete specimen in a low-concentration salt solution to simulate the dynamic migration and diffusion process of salt.

[0041] Specifically, step S3 includes: Step S31: Apply a low-concentration salt solution with a total salt concentration of 0.1 times that of standard seawater; the low-concentration salt solution contains Cl... - SO4 2- Mg 2+ The concentrations are 0.1 times the corresponding ion concentrations in the high-concentration salt solution; the duration of step S3 is 7 to 30 days.

[0042] Specifically, the specimen after step S2 is immersed in a low-concentration salt solution. The total salt concentration of the low-concentration salt solution is 3.5 g / L (i.e., 0.1 times the standard seawater salt concentration of 35 g / L). Its ion composition is consistent with that of the high-concentration salt solution, with Cl... - SO4 2- Mg 2+ The molar concentration ratio remains 7:5:2, but the absolute concentrations are both 0.1 times the corresponding ion concentrations in the high-concentration solution. For example, if the high-concentration solution contains Cl... - If the concentration is 0.7 mol / L, then the Cl concentration in this stage is... - The concentration was 0.07 mol / L. The solution was prepared at this ratio, and the specimens were completely immersed in it for 7 to 30 days. This environment promoted the outward diffusion of high-concentration salts remaining inside the concrete from step S1, while low-concentration salts migrated inward, forming a bidirectional ion flow. This process realistically simulated the dynamic leaching and re-enrichment cycle of salts in saline soil caused by rainfall or changes in groundwater level, and is key to reproducing long-term salt migration behavior.

[0043] Step S32: The ionic composition of the low-concentration salt solution is the same as that of the high-concentration salt solution, but the concentration is significantly reduced.

[0044] Specifically, this step further specifies the consistency of ion composition in step S31. Regardless of whether the concentration is high or low, the corrosive ion is Cl. - SO4 2- Mg 2+ The concentration was maintained at a constant 7:5:2 molar ratio. This design ensured that the type of ion erosion experienced by the concrete was continuous and consistent throughout the entire test period, avoiding atypical reactions that might be caused by changes in ion types. Variations in concentration only simulated fluctuations in the salt content of the environment, not changes in the type of salt.

[0045] Step S33: The high-concentration salt solution and the low-concentration salt solution are applied alternately according to a set cycle to form a low-frequency switching.

[0046] Specifically, steps S1 and S3 form an alternating closed loop. For example, after a complete "S1→S2→S3" sequence, it can start again from step S1, forming multiple cycles. The switching period T refers to the time between the start of one high-concentration stage and the start of the next high-concentration stage, and its value is not less than 7 days. The switching frequency f=1 / T, not greater than 0.14 times / day. Low-frequency switching ensures sufficient relaxation time for ion migration and reaction within each concentration stage, approximating the quasi-static process of salt changes in the real environment. In a preferred embodiment, when step S1 lasts for 20 days, step S3 lasts for 10 days, and step S2 is performed 10 dry-wet cycles, it constitutes a complete experimental unit with a total duration of 980 hours. This low-frequency configuration has been verified by long-term exposure data and can effectively reproduce the salt migration pattern.

[0047] Step S34: The test method does not collect or analyze parameters related to steel corrosion; all performance evaluations are based on the concrete itself, including: XRD quantitative phase analysis, MIP pore structure test, three-point bending strength, fracture energy and microcrack connectivity under scanning electron microscopy (SEM).

[0048] Specifically, after step S3 or at a specific point in the experiment, the performance of the concrete specimens was evaluated. X-ray diffraction (XRD) was used to quantitatively analyze changes in the content of phases such as Ca(OH)2, CSH, and ettringite; mercury intrusion porosimetry (MIP) was used to test pore size distribution, total porosity, and critical pore size; a three-point bending test (300 mm span, 0.05 mm / min loading rate) was used to determine flexural strength and fracture energy; and scanning electron microscopy (SEM) was used to observe microcrack development, and image processing software was used to calculate the connectivity probability of the microcrack network. All evaluation indicators focused on the concrete material itself, aiming to systematically reveal the evolution of the microstructure and macroscopic properties of concrete under the coupling effect of salt crystallization and chemical dissolution, providing data support for material composition design.

[0049] By executing steps S31 to S34, step S3 works in conjunction with steps S1 and S2 to form a complete closed-loop evaluation system for the synergistic evolution of chemical dissolution, physical erosion, and ion transport. Its overall beneficial effect is to efficiently and realistically reproduce the entire process of concrete material performance degradation in saline soil environment.

[0050] The foregoing has shown and described the basic principles, main features, and advantages of this invention. Those skilled in the art should understand that this invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of this invention. Various changes and modifications can be made to this invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the claimed invention. The scope of protection of this invention is defined by the appended claims and their equivalents.

Claims

1. A method for accelerating the testing of low-frequency, high-concentration salt-eroded concrete, characterized in that, The closed-loop test process consists of the following three stages: Step S1: Apply a high-concentration salt solution to the surface of the concrete specimen to form visible salt crystals on the surface and in the pores near the surface of the specimen; Step S2: After completing step S1, the concrete specimen is subjected to a dry-wet cycle treatment based on a chemical solvent, so that calcium hydroxide Ca(OH)2 in the concrete reacts with calcium silicate hydrate CSH to generate soluble calcium salts. Step S3: Immerse the concrete specimen in a low-concentration salt solution to simulate the dynamic migration and diffusion process of salt. The high-concentration salt solution and the low-concentration salt solution are applied alternately at a set period to form a low-frequency switching; the solution flow rate is adjusted throughout the test to act on the surface of the specimen to simulate the physical disturbance caused by groundwater seepage or tidal erosion; the entire closed-loop test process constitutes an accelerated test system that integrates chemical action, physical damage and ion transport, and is used to guide the design of concrete material composition.

2. The method according to claim 1, characterized in that, In step S1, the high-concentration salt solution contains Cl. - SO4 2- Mg 2+ Furthermore, the three components coexist in a fixed molar ratio; in step S2, the chemical solvent is NH4Cl, which provides soluble ions during the wet-dry cycle wetting stage; in step S3, the ionic composition of the low-concentration salt solution is the same as that of the high-concentration salt solution, but the concentration is significantly reduced.

3. The method according to claim 1, characterized in that, The alternation between step S1 and step S3 satisfies the low-frequency condition: the switching period T is not less than 7 days, and the switching frequency f is expressed as f = 1 / T, and is not greater than 0.14 times / day; the solution flow rate ranges from 0.5 m / s to 2.0 m / s.

4. The method according to claim 1, characterized in that, Step S1 specifically includes: applying a salt solution with a total salt concentration of 5 to 10 times that of standard seawater, wherein the standard seawater salt concentration is 35 g / L; the high-concentration salt solution contains Cl... - SO4 2- Mg 2+ The molar ratio is 2:5:2; the duration of step S1 is 7 to 30 days.

5. The method according to claim 1, characterized in that, Step S2 specifically includes: after step S1, the specimen is placed in a constant temperature and humidity environment to dry for 24 hours, and then immersed in NH4Cl solution for 2 hours to form a dry-wet cycle; the cycle is repeated 5 to 10 times; the molar concentration of the NH4Cl solution is 0.5 mol / L to 2.0 mol / L; the pH value of the NH4Cl solution is maintained at 4.5±0.

2.

6. The method according to claim 1, characterized in that, Step S3 specifically includes: applying a low-concentration salt solution with a total salt concentration of 0.1 times that of standard seawater; wherein the low-concentration salt solution contains Cl... - SO4 2- Mg 2+ The concentrations are 0.1 times the corresponding ion concentrations in the high-concentration salt solution; the duration of step S3 is 7 to 30 days.

7. The method according to claim 1, characterized in that, The solution flow rate remains stable when both the high-concentration salt solution and the low-concentration salt solution are applied, and the fluctuation range does not exceed ±0.1 m / s; the solution flow rate is set so that the shear stress on the surface of the specimen is maintained within the range of 0.8 Pa to 3.2 Pa.

8. The method according to claim 1, characterized in that, The concrete specimens were prepared using the actual engineering mix proportions, with a water-cement ratio not exceeding 0.

45. After standard curing for 28 days, the specimens were dried in a 60°C oven to constant weight before entering the first stage of testing.

9. The method according to claim 1, characterized in that, The experimental method does not collect or analyze parameters related to steel corrosion; all performance evaluations are based on the concrete itself, including: XRD quantitative phase analysis, MIP pore structure test, three-point bending strength, fracture energy, and microcrack connectivity under scanning electron microscopy (SEM).